Kimbanguism: its present Christian doctrine and the problems raised by it - Nguapitshi Kayongo, Léon (Exchange, 2005)
Although the present publication does completely meet the requirements for an academic article, we have decided to publish it because of the insights it provides into the latest developments within the Kimbanguist Church in Congo. The author is a theologian who was Dean of the Kimbanguist Faculty of Theology in Lutendele near Kinshasa until mid 2003. He was deeply involved in the problems that arose in the beginning of the 21st century. He is also a person who is able to explain diligently the views of the different parties in the Kimbanguist Church. However, due to his own involvement in these developments the article has rather the character of a document written by a well-educated participant observer, who is very familiar with his subject, than that of a publication authored by a scholar who does his utmost to remain neutral.The document explains the theological, religious and contextual backdrops of the doctrine of the Trinity developed in the Kimbanguist Church, for in this church the persons of the Trinity are narrowly connected with the founder of the church and his family. Since 2001 these connections were even made more intense. Interestingly there are some Biblical reasons for it as well, but nonetheless the church seems to loose doctrinal familiarity with the other churches in the world through these new evolutions.
Paid
Keywords: Controversies; Ecclesiastical; Eglise de Jésus-Christ sur la terre par le prophète Simon Kimbangu; Kiangani Dialungana; Salomon; 1916-2001; Kimbangu; Simon; 1889?-1951; Kimbanguism; Kuntima; Joseph Diangienda; Leadership; Religious – Christianity; Lukelo; Charles Kisolokele; Peer reviewed; Theology; Doctrinal – 2000